PTU-057 Inflammatory bowel disease and the risk of thromboembolic disease. (22nd June 2015) - Kumar, A; Disney, BR; Wood, L; Slater, J; de Silva, S
Abstract : Introduction: Patients with inflammatory bowel disease (IBD) are thought to be associated with an increased risk of developing venous thromboembolic (VTE) disease and arterial thrombi (AT). There is conflicting data on the prevalence of VTE disease and AT in IBD, varying between 1.2% and 6.7% in clinical studies, which rises to 39% in postmortem studies. Our aims were to evaluate the rate and risk factors of VTE and AT in a large cohort of IBD patients. Method: We performed a retrospective review between the years 1984 to 2014 of all patients with IBD. These patients were identified from the IBD database and cross-referenced with the online electronic reporting system, patient notes and clinic letters. Results: There were a total of 1678 patients with IBD, with 47 found to have VTE and AT, giving a prevalence rate of 2.8%. Of these 47 patients, 8 (17%) patients had recurrent disease with 6 (12.8%) patients having 2 incidents and 2 (4.2%) patients having 3 incidents of VTE disease. The median age was 60.2 years old with a greater risk for males than females (55% vs. 45%) and with ulcerative colitis than Crohn's disease (2.8% vs. 0.87%). 36 (2.1%) patients were diagnosed with deep venous thrombosis (DVT) and 20 (1.2%) with pulmonary embolism (PE). The remaining four had portal vein thrombosis, common femoral artery occlusion, femoral artery embolus and superficial femoral artery occlusion. Three patients were diagnosed with both DVT and PE in the same admission. The average duration from time of IBD diagnosis to VTE and AT confirmation was 7.4 years. 5 patients were identified with VTE prior to their IBD diagnosis. At the time of their diagnosis, 3 (5.3%) patients were treated for malignancy in the previous six months and 4 (7%) had undergone surgery in the previous four weeks. 32 (56%) patients were being treated with 5-aminosalicylic acid (5ASA) drugs, 17 (30%) with azathioprine, 12 (21%) with oral steroids, 4 (7%) with intravenous (IV) steroids, 2 (4%) had infliximab and 1 (2%) had adalimumab. Blood tests at time of diagnosis showed a median CRP of 46 and platelet count of 345. The mortality rate was 10.6%, of which one death was directly related to their VTE. 10.5% underwent surgery, 63% were anticoagulated and 1.8% underwent failed tissue plasminogen activator (TPA) therapy. 3.5% were left with a disability secondary to their VTE disease. Conclusion: Thromboembolic disease is an increasingly prevalent and preventable complication of IBD. Positive risk factors identified in our cohort were patients that were male, increasing age and diagnosis of ulcerative colitis. Considering almost one third of those diagnosed were receiving oral or IV steroid therapy and had an average raised CRP, this supports the view that a disease flare is an ongoing risk factor for developing VTE and AT. Disclosure of interest: None Declared.